Effectiveness of Compassion-Focused Therapy on Emotion Regulation and Fear of Intimacy in Women Affected by Marital Infidelity - Fadai Moghadam , Zahra; Mehri, Saadat; Dehghani , Mahsa; Gholami , Amin Allah; Gholami, Forud (Mental Health and Lifestyle Journal, 2024)
The aim of this study was to evaluate the effectiveness of Compassion-Focused Therapy (CFT) on emotion regulation and fear of intimacy in women affected by marital infidelity. This study was conducted as a randomized controlled trial and included 30 women aged 25 to 45 years residing in Tehran who had reported experiences of marital infidelity. Participants were randomly assigned to an intervention group (n=15) and a control group (n=15). The intervention group received a 12-session Compassion-Focused Therapy program, while the control group was placed on a waitlist. To assess emotion regulation and fear of intimacy, the Cognitive Emotion Regulation Questionnaire (CERQ) and the Fear of Intimacy Scale (FIS) were administered at three time points: pre-test, post-test, and 5-month follow-up. The results indicated that the intervention group demonstrated significantly greater improvements in emotion regulation and reductions in fear of intimacy compared to the control group. Repeated measures ANOVA showed that these changes in both variables remained statistically significant at the post-test and follow-up stages (p < 0.001). Furthermore, the intervention produced a marked reduction in emotional turmoil and fear of intimacy in the intervention group. Compassion-Focused Therapy proved to be effective in enhancing emotion regulation and reducing fear of intimacy in women affected by marital infidelity. The positive effects of this intervention were sustained over time, indicating the potential of CFT as a long-term therapeutic approach. These findings suggest that CFT may be an effective strategy for addressing emotional and relational challenges resulting from infidelity.